Inhibitors of Bacterial Transcription are Compounds for Potent Antimicrobial Drugs - Turecka, Katarzyna; Waleron, Krzysztof (Current Pharmaceutical Biotechnology, 2013)
The increasing resistance of microorganisms against antibiotics available on the pharmaceutical market is now a global problem. There is an incessant necessity to search for new, effective treatments against resistant strains of microorganisms, for new potent classes of antibiotics with novel modes of action targeted at important components of microbial cells. Such a critical, essential system for cell functioning is a RNA polymerase (RNAP), an enzyme that catalyses one of the stages of gene expression: transcription. RNAP is a proven target for a number of antibiotics, and it still remains an attractive drug target for new potent antimicrobial compounds. In this review several examples of inhibitors for transcription and RNAP are presented.
Keywords: inhibitors